The intrigue in Ricardo Palma's stories - Chiri Jaime, Sandro (2019)
The intrigue plays a crucial part in the Traditions that Ricardo Palma writes for over half a century. It functions as an articulating axis of the great historical fictional mosaic that the 19th-century Peruvian writer imposes on himself as a personal and artistic challenge as well as a legacy for his readers. The following work tracks Palma’s contributions in these areas of the art of storytelling.